Soil microbial activity, yield and grain quality of rice (Oryza sativa L.) as influenced by graded doses of fluoride in Alfisols - Panda, N; Dash, A K; Nayak, B R; Sarangi, N (ORYZA-An International Journal of Rice, 2018)
A field experiment was conducted at Regional Research and Technology Transfer Station (RRTTS),Chiplima, OUAT, during 2014-15 and 2015-16 to study the impact of graded doses of fluoride on soil microbial activity, yield and grain quality of rice. Six doses of fluoride i.e., No fluoride, 100, 150, 200, 250 and 300 ppm F in form of hydrofluoric acid (HF) were applied as foliar spray. Highest grain (36.73 q/ha) and straw (47.34 q/ha) yield of rice was recorded with T1 (No fluoride) where as lowest grain (32.90 q/ha) and straw (40.09 q/ha) yield was observed with T6 (foliar spray of F @ 300 ppm as HF). The grain yield was decreased significantly with increasing doses of fluoride. The decrease in grain yield was highest (10.42 %) with T 6 (foliar spray of F @ 300 ppm as HF) over control (T1 = No fluoride) where a lowest value of 3.02 % was observed Significantly highest total chlorophyll content (4.53 mg/ g fresh leaf) was observed with T 1 which was decreased to lowest value of 2.26 mg/ g fresh leaf (T6) due to increasing doses of fluoride. The lowest value with respect to leaf area index (4.18), grain length (4.38 mm), kernel elongation (6.18 mm), plant height (123.78 cm ) and panicle length (22.28 cm ) was recorded with T6 (foliar spray of F @ 300 ppm as HF). Howeverhighest F uptake (24.71 kg/ha)was recorded with foliar spray of F @ 300 ppm as HF (T6).The variation in grain quality parameters such as protein content (R2=0.982), amylose content (R2=0.981) and alkali value (R2=0.839) were significant due toincrease in F doses. Soil microbial biomass carbon (MBC), soil dehydrogenase activity (DHA) and soil bacterial population were decreased with increased doses of F irrespective of crop growth stages